Particulate matter impairs immune system function by up‑regulating inflammatory pathways and decreasing pathogen response gene expression (2023)
ABSTRACT: Airborne particulate matter produced by industrial sources and automobiles has been linked to increased susceptibility to infectious diseases and it is known to be recognized by cells of the immune system. The molecular mechanisms and changes in gene expression profiles induced in immune cells by PM have not been fully mapped out or systematically integrated. Here, we use RNA-seq to analyze mRNA profiles of human peripheral blood mononuclear cells after exposure to coarse particulate matter (PM10). Our analyses showed that PM10 was able to reprogram the expression of 1,196 genes in immune cells, including activation of a proinflammatory state with an increase in cytokines and chemokines. Activation of the IL-36 signaling pathway and upregulation of chemokines involved in neutrophil and monocyte recruitment suggest mechanisms for inflammation upon PM exposure, while NK cell-recruiting chemokines are repressed. PM exposure also increases transcription factors associated with inflammatory pathways (e.g., JUN, RELB, NFKB2, etc.) and reduces expression of RNases and pathogen response genes CAMP, DEFAs, AZU1, APOBEC3A and LYZ. Our analysis across gene regulatory and signaling pathways suggests that PM plays a role in the dysregulation of immune cell functions, relevant for antiviral responses and general host defense against pathogens.